Use of web-based game in neonatal resuscitation - is it effective? - Yeo, Cheo Lian (2020)
Background: Knowledge and skills decline within months post simulation-based training in neonatal resuscitation. To empower ‘Millennial’ learners to take control of their own learning, a single-player, unguided web-based Neonatal Resuscitation Game was designed. The present study investigates the effectiveness of the game on retention of resuscitation knowledge and skills. Methods: The study evaluated 162 healthcare professionals who attended simulation-based training in neonatal resuscitation. Following standard simulation-based training, participants were assigned to either a gaming group (Gamers) with access to the web-based Neonatal Resuscitation Game or a control group (Controls) with no access to the game. Although Gamers were given access, game utilization was completely voluntary and at will. Some Gamers chose to utilize the web-based game (Players) and others did not (Non-players). Knowledge and skills in neonatal resuscitation were assessed upon completion of training and 6 months post-training using a multiple-choice question test and a manikin-based skills test. Changes in scores were compared statistically between Gamers vs Controls, Players vs Controls, and Players vs Controls + Non-players using two-sample t-tests. Results: At the final assessment, declines in knowledge scores were seen in all groups. Mean change from baseline in knowledge and skill performance scores at 6 months, adjusted for baseline skill performance and MCQ test scores, did not differ significantly between Players vs Controls and Players vs Controls + Non-players. Conclusion: The web-based game in its current format may not be effective in facilitating retention of knowledge and technical skills in neonatal resuscitation.